"Clickable" and Antifouling Block Copolymer Brushes as a Versatile Platform for Peptide-Specific Cell Attachment - Poręba, Rafał; de Los Santos Pereira, Andres; Pola, Robert; Jiang, Siyu; Pop-Georgievski, Ognen; Sedláková, Zdeňka; Schönherr, Holger (Macromolecular bioscience, 2020)
To tailor cell-surface interactions, precise and controlled attachment of cell-adhesive motifs is required, while any background non-specific cell and protein adhesion has to be blocked effectively. Herein, a versatile and highly reproducible antifouling surface modification based on "clickable" groups and hierarchically structured diblock copolymer brushes for the controlled attachment of cells is reported. The polymer brush architecture combines an antifouling bottom block of poly(2-hydroxyethyl methacrylate) poly(HEMA) and an ultrathin azide-bearing top block, which can participate in well-established "click" reactions including the highly selective copper-catalyzed alkyne-azide cycloaddition (CuAAC) reaction under mild conditions. This straightforward approach allows the rapid conjugation of a cell-adhesive, alkyne-bearing cyclic RGD peptide motif, enabling subsequent specific attachment of NIH 3T3 fibroblasts, their extensive proliferation and confluent cell sheet formation after 48 h of incubation. The generally applicable strategy presented in this report can be employed for surface functionalization with diverse alkyne-bearing biological moieties via CuAAC or copper-free alkyne-azide cycloaddition protocols, making it a versatile functionalization approach and a promising tool for tissue engineering, biomaterial implant design, and other applications that require surfaces supporting highly specific cell attachment.
Keywords: alkyny; Biocompatible Materials; buňky NIH 3T3; NIH 3T3 Cells; katalýza; Cycloaddition Reaction; tkáňové podpůrné struktury; Oligopeptides; Tissue Engineering; surface biofunctionalization; antiinfekční látky; antifouling; Anti-Infective Agents; oligopeptidy; Catalysis; biokompatibilní materiály; Mice; Cell Proliferation; copolymer brushes; cykloadiční reakce; click chemie; azidy; Tissue Scaffolds; controlled-cell attachment; Azides; zvířata; tkáňové inženýrství; Polyhydroxyethyl Methacrylate; myši; proliferace buněk; polyhydroxyethylmethakrylát; Alkynes; Click Chemistry; Animals